MANAJEMEN PEMASARAN PRODUK WISATA KAPAL PESIAR PT. AVS INDONESIA - Tasya, Nanda; Nugraha, DKN (UI Scholars Hub, 2018)
Cruises become a new option for travelers to travel with ease, with diverse destinations and lot’s of activities to do. Ships used exclusively for recreational purposes. Such as Costa Cruises, Princess Cruises, Royal Caribbean International, Oceania Cruises, and many others. With diverse of facilities that can be enjoyed on board, cruise ship tours become one of the best choice for tourists who want to relax and enjoy the beauty of the sea. Each brand has different products, facilities, and destinations according to their individual characteristics. Similarly, the marketing and sales strategies implemented. Each brand releases it’s products with a variety of attractive promotions that are biased on offer to tourists. Likewise with PT. AVS INDONESIA which is a company engaged in tourism, especially in the field of travel such as air transportation and travel services.